Peliosanthes nagalandensis and P. tobuensis (Asparagaceae: Nolinoideae)—two new species from Northeastern India - Odyuo, Nripemo; Roy, Dilip Kr.; Lytan, Rikertre; Tanaka, Noriyuki; Mao, Ashiho A. (Phytotaxa, 2020)
Two new species of Asparagaceae (subfamily Nolinoideae), Peliosanthes nagalandensis and P. tobuensis, from the state of Nagaland, Northeastern India, are described and illustrated. P. nagalandensis is most closely related to P. arunachalensis, but differs mainly by the longer leaf blades, distinctly sigmoid flowering stem with a shorter peduncle and longer raceme, more numerous green to purple flowers, distally finely denticulate-erose perianth segments, basally hamately recurved anthers and papillulate pistil with an apically slightly concave ovary and a columnar style. While P. tobuensis is close to P. arunachalensis and P. sinica, but differs mainly by the strongly incurved, entire corona and ovoid pistil with obtusely conical indistinct style.